Safety and effectiveness of open pancreaticoduodenectomy in adults aged 70 or older: A meta-analysis. Issue 7 (September 2021) - Zhang, Wei; Huang, Zhangkan; Zhang, Jiangwei; Che, Xu
Abstract: Background: Pancreaticoduodenectomy (PD) is considered the most complicated operation in abdominal surgery. The safety and effectiveness of PD in older patients has been questionable because older adults are often beset by one or more systemic diseases and have poor surgical tolerance. Aim: To evaluate the safety and effectiveness of PD in patients aged 70 or older. Methods: We conducted a literature search on PubMed, EMBASE, Cochrane Library and other databases to discover all literature reporting a comparison of the efficacy of PD in patients 70 years old and older versus patients under 70 years old. Our cutoff date is August 2020. Revman5.3 statistical software was used for the analysis. Results: Twenty cohort studies were determined to be eligible with a total of 6508 patients; 2274 patients were 70 years old and older and 4234 patients under 70 years old. Meta-analysis results showed that after PD in patients over 70 years of age and older the mortality rate ( RR = 2.1, 95%CI:1.59–2.78, p < 0.001), the overall postoperative complications ( RR = 1.16, 95%CI:1.09–1.23, p < 0.001), intraoperative transfusions ( RR = 1.38, 95%CI:1.14–1.23, p = 0.001), severe complications ( RR = 1.30, 95%CI:1.11–1.52, p = 0.001), the re-operation rate ( RR = 1.23, 95%CI:1.00–1.51, p = 0.05), the R0 rate (RR = 0.92, 95%CI:0.86–0.98, p = 0.01), lymph node dissection ( WMD = −4.61, 95%CI:−7.24–1.97, p < 0.001) and delayed gastric emptying ( RR = 1.24, 95%CI:1.04–1.49, p = 0.02) at a rate significantly higher than that of patients under 70 years old. There is no significant difference between patients 70 years old and older and patients under 70 years old in the clinical PF ( RR = 1.11, 95%CI:0.93–1.34, p = 0.24), bile leakage ( RR = 0.68, 95%CI:0.41–1.12, p = 0.13), postoperative bleeding ( RR = 1, 95%CI:0.76–1.30, p = 0.98), wound infection ( RR = 1.15, 95%CI:0.95–1.39, p = 0.15) and hospital stays ( RR = 0.30, 95%CI:−1.77–2.37, p = 0.77). Conclusion: Patients aged 70 years or older have approximately double the risk of postoperative mortality following PD and a higher risk of overall and severe postoperative complications. Furthermore, patients 70 years old and older require more frequent intraoperative transfusions, re-operative interventions and have poorer oncology results (lower R0 rate and fewer lymph node dissections). More multi-center, large sample, and high-quality research is still needed to further verify this conclusion.